Внутриствольное строение нервов половых органов некоторых пушных животных - Прядко, В.П. (Вестник зоологии, 1977)
There are cases of asymmetry in the nerve structure of the Alopex lagopus L. female genitals: area of the nerve cross-section and the number of nerve fibre bundles in the right and left similar nerves are different in the same animal. Individual variation in these indexes might be associated with the degree of connective tissue development in the nerve trunks. Each nerve has nerve fibre bundles of different diameters consisting primarily of nonmedullated nerve fibres. The number of medullated nerve fibres is not large. Their presence in the nerve trunks indicates that peripheral nerves in the Alopex lagopus females are of the mixed type because they are composed by both medullated and nonmedullated nerve fibres.